COMMUNICATIVE LANGUAGE TEACHING (CLT) APPROACH IN MODERN LANGUAGE EDUCATION: PRINCIPLES, CHALLENGES AND PRACTICAL APPLICATIONS - Pardayeva Sevinch,; Odiljonova Asal, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract   Communicative Language Teaching (CLT) is an approach to language teaching that  emphasizes  interaction  as  both  the  means  and  the  ultimate  goal  of  learning  a language.  This  article  provides  an  extensive  analysis  of  the  CLT  methodology, focusing  on  its  implementation  in  contemporary  educational  settings.  The  study explores  how  CLT  shifts  the  focus  from  traditional  grammatical  competence  to communicative competence, enabling learners to use the language effectively in real-life interpersonal exchanges. This comprehensive review discusses the core principles of the approach, such as student-centered learning, the use of authentic materials, and the critical balance between fluency and accuracy. Furthermore, the article delves into the specific classroom activities that facilitate active communication, including role-plays, information gaps, and collaborative problem-solving tasks. Despite its widely recognized benefits in improving speaking and listening skills, the implementation of CLT  is  not  without  challenges.  The  paper  addresses  significant  hurdles  such  as managing large class sizes, the transition for teachers trained in traditional methods, and  the  complexities  of  assessing  communicative  proficiency.  Through  a  detailed examination of current pedagogical theories by scholars like Richards, Rodgers, and Brown,  this  article  argues  that  CLT  remains  a  vital  and  dynamic  framework  for language acquisition in a globalized world. The findings suggest that while a hybrid approach  might  be  necessary  for  certain  contexts,  the  fundamental  communicative goals of CLT are essential for developing true linguistic autonomy. This article aims to provide educators with a clear blueprint for integrating CLT strategies into their daily teaching practice to enhance student engagement and outcomes.